Monitoring Suhu dan Kelembaban Ruangan Server di BSPJI Palembang Menggunakan Microcontrol Arduino Berbasis Android - Prayuda, Rizki Budi; Jambak, Muhammad Ikhwan; Mair, Zaid Romegar (Jurnal Pengembangan Sistem Informasi dan Informatika, 2023)
This research aims to develop a temperature and humidity monitoring system for the server room at the Palembang Industrial Standardization and Services Center (BSPJI) using an Android-based microcontroller. This system monitors server room environmental conditions in real-time to maintain equipment performance and reliability. The microcontroller integrated with the Android application can collect temperature and humidity data using appropriate sensors, which can be accessed and analyzed remotely via the Android application. Temperature and humidity measurement results can also be forwarded via in-app notifications to notify users of abnormal conditions. This research combines microcontroller technology, environmental sensors, and Android applications to provide a monitoring solution that is effective and responsive to environmental changes in the server room. Hopefully, this system can help maintain server stability and performance at BSPJI more efficiently